Plan estratégico para la organización Woofme spa y boutique con un horizonte de tiempo 2021 - 2024 (2020)
This work addresses the development of a strategic plan for the Woofme Spa and Boutique organization, with the aim of directing a relevant process that will contribute to its consolidation over the next three years, with competitive dynamics and with value generation for its interest groups, and also presents the results of strategic planning and the challenges it has to take on from the organizational direction, allowing a transformation of the This document compiles the instruments used, strategic objectives, short-term organizational bets and the budget required for the implementation of the action plan that will enable the purposes of the management of Woofme Spa & Boutique to be fulfilled, through the review of trends and the way of operation of market leaders.